A novel navigation algorithm for collaborative multi robots - Ahmed, Mohiuddin; Khan, Md. Raisuddin; Billah, Md. Masum; Farhana, Soheli (EuroJournals Publishing, 2010)
Robots are playing an increasingly more important role as the technology is maturing. Robots are omnipresent; numerous robots committed to a single task will become ordinary. Multi-agent robots are capable of handling problems in many different ways than individuals while achieving higher levels of performance. But present unique challenges for developing collaborative navigation algorithm and coordination among themselves are not sufficient for autonomous collaborative tasks. Some research papers based on collaborative robots have been reviewed in this paper; from review analysis we have developed an algorithm with behavioral based distributed knowledge of multi-agents for accomplishing collaborative navigation. The goal of multi-agent robots is to move as a cohesive team by sharing their distributed learning behaviors and navigating in autonomous reconnaissance missions. Finally some preliminary experimental results will be presented of the developed collaborative navigation algorithm between robots to reach the target and achieve their goal sharing their knowledge..